Natural particles can armor emulsions against lipid oxidation and coalescence. (15th June 2021) - Schröder, Anja; Laguerre, Mickaël; Tenon, Mathieu; Schroën, Karin; Berton-Carabin, Claire C.
Highlights: Particles naturally occurring in plant by-streams were used to formulate emulsions. Moderately hydrophobic natural particles can physically stabilize O/W emulsions. Matcha tea and spinach leaf powder-stabilized emulsions were highly stable to lipid oxidation. Natural Pickering particles are promising for formulating clean-label food emulsions. Abstract: Traditional functional ingredients, such as conventional emulsifiers (surfactants, animal-derived proteins), and synthetic antioxidants may become obsolete in the development of clean-label, plant-based, sustainable food emulsions. Previously, we showed that tailor-made antioxidant-loaded particles can yield both physically and oxidatively stable emulsions, and we expected that natural particles with related properties could also show these beneficial effects. Here, we investigated Pickering emulsions prepared with natural plant particulate materials. Particles that showed weak aggregation in acidic aqueous media, indicating a relatively hydrophobic surface, were able to physically stabilize oil-in-water emulsions, through either Pickering stabilization (powders of matcha tea, spinach leaves, and spirulina cake), or an increase in viscosity (pineapple fibers). Matcha tea and spinach leaf particle-stabilized emulsions were highly stable to lipid oxidation, as compared to emulsions stabilized by conventional emulsifiers. Taking this dual particle functionality as a starting point for emulsion design is, in our view, essential to achieve clean-label food emulsions.